Beyond abuse and neglect: validation of the childhood interpersonal trauma inventory in a community sample of adults - Legendre, Maxime; Milot, Tristan; Rousseau, Michel; Lemieux, Roxanne; Garon-Bissonnette, Julia; Berthelot, Nicolas (Frontiers in Psychiatry, 2024)
Introduction Childhood trauma is not restricted to abuse or neglect and other potentially traumatic experiences need to be pondered in practice and research. The study aimed to collect validity evidence of a new measure of exposure to a broad range of potentially traumatic experiences, the Childhood Interpersonal Trauma Inventory (CITI), by evaluating whether the CITI provides important additional information compared to a gold standard measure of childhood trauma. Methods The sample consisted of 2,518 adults who completed the CITI and self-reported measures of trauma (Childhood Trauma Questionnaire; CTQ) and psychiatric symptoms (PTSD Checklist for DSM-5; Kessler Psychological Distress Scale; Dissociative Experiences Scale). Results First, the sensitivity to properly detect participants having been exposed to childhood maltreatment, as measured by the CTQ (here used as the gold standard), ranged between 64.81% and 88.71%, and the specificity ranged between 68.55% and 89.54%. Second, hierarchical regressions showed that the CITI predicted between 5.6 and 14.0% of the variance in psychiatric symptoms while the CTQ only captured a very small additional part of variance (0.3 to 0.7%). Finally, 25% (n = 407) of CTQ-negative participants screened positive at the CITI. The latter reported higher severity of psychiatric symptoms than participants without trauma, suggesting that the CITI permits the identification of adults exposed to significant traumas that remain undetected using other well-validated measures. Discussion The findings underscore the utility of the CITI for research purposes and the latter’s equivalence to a gold standard self-reported questionnaire to predict negative outcomes.